(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
In this article describes various methods used in teaching English to students, effective strategies and approaches to make the process of teaching English engaging, interactive, and impactful, highlighting their strengths and considerations for effective implementation.